The management of methamphetamine use in sexual settings among men who have sex with men in Malaysia - Lim, Sin How; Akbar, Mohd; Wickersham, Jeffrey A.; Kamarulzaman, Adeeba; Altice, Frederick L. (Elsevier, 2018)
Background: The intentional use of illicit drugs for sexual purposes (also known as ‘chemsex’) is well known within the MSM communities in Malaysia although research in this population is scarce primarily because both drug use and homosexuality are illegal and stigmatised in Malaysia. Methods: From April to December 2014, interviews were conducted with twenty men (age range 21–43) living in Greater Kuala Lumpur who had sexual intercourse with other men in the past 6 months and who used illicit drugs at least monthly in the past 3 months. Fourteen men were recruited via gay social networking smartphone applications or websites while six were referred by the participants. Data were analsed using thematic analytic approach. Findings: The average duration of illicit drug use was 6.4 years (range 1–21) and all participants were using methamphetamine (“ice” or crystal meth) with frequency of use ranged from daily to once a month. Participants came from diverse ethnic, economic, and occupational backgrounds. Most participants used an inhalation apparatus (“bong”) to consume methamphetamine and injection was rare in the sample. The primary motivation of methamphetamine use was to increase sexual capacity, heighten sexual pleasure and enhance sexual exploration and adventurism. Socializing with friends (“chilling”), and increased energy for work were secondary motivations. Participants emphasized the need to control the use of methamphetamine and some have established rules to control the amount and duration of use and a minority of men have maintained condom use during anal sex while under the influence of methamphetamine. Participants who professed to be in control of their drug use characterized themselves as functional users regardless of the health and social consequences from continuing use. Overall, participants perceived themselves differently from the traditional opioid users and reported limited access to sexual health and substance use treatment services. Conclusion: There is a need to increase access to HIV prevention services such as PrEP and PEP, professional support, and substance abuse treatment for drug-using MSM. A more open and friendly environment towards drug-using MSM may help them access and engage with the health services.